Public Service Standards Nurse Practice License at the Investment Office and One-Stop Integrated Services of Bengkalis Regency - Evi Lastiur Tampubolon; Harapan Tua RFS (Jurnal Ilmiah Wahana Pendidikan, 2023)
The value of compliance with public service standards in Bengkalis Regency in 2021 increased to the green zone. This is quite proud because, in the 2019 assessment, the compliance value is still in the yellow zone. This study aims to see how the implementation of public service standards in DPMPTSP which is one of the public servants in Bengkalis Regency and what are the supporting factors. The theory used is the theory of public service standards according to Ridwan & Sudrajat (2009), namely service procedures, completion times, service products, facilities and infrastructure, and the competence of service officers. Data collection is done through observation, interviews, and documentation. The results show that the implementation of public service standards has been implemented well although there are still some things that need to be improved. Then it can be known the supporting factors, namely organizational factors and supervisory factors.